PENGEMBANGAN MEDIA PEMBELAJARAN E-LEARNING BERBASIS WEB MATERI ALJABAR KELAS VII DI MTS MIFTAHUL ULUM PROBOLINGGO - Abdur Rofiq; Tuhfatul Janan (Koordinat Jurnal MIPA, 2023)
Science and technology are currently experiencing rapid development. Today, the learning is not only limited to conventional methods, but also allows online learning through the development of website-based learning media. Through this media, learning materials can be accessed easily and flexibly, without geographical or time restrictions. This research aims to create mathematics learning media that focuses on Algebra topics. The research method used is Research and Development (RnD) by following the ADDIE approach. The results of this research are tangible in the form of a web-based e-learning platform that presents Algebra material for grade VIII junior high school students. This media tested by grade VII students at MTs Miftahul Ulum Probolinggo test results show that this product can be considered valid and the results of the trial showed that the assessment by media experts obtained a percentage score of 92%, in terms of the content of the material on the website, a percentage score of 88% was obtained by material experts. Meanwhile, in field testing carried out by students, they got a percentage score of 71.7%.